Associations of delta fatty acid desaturase gene polymorphisms with lipid metabolism disorders - Oksana Yu. Kytikova; Tatyana P. Novgorodtseva; Yulia K. Denisenko; Marina V. Antonyuk; Tatyana A. Gvozdenko (Russian Open Medical Journal)
Overweight, obesity, type 2 diabetes mellitus, metabolic syndrome, cardiovascular diseases, and non-alcoholic fatty liver disease are common chronic ailments associated with lipid metabolism disorders. One of the mechanisms of these disorders is related to the deficiency and/or change in the balance of essential fatty acids (FAs). At the same time, the provision of ω3 and ω6 polyunsaturated fatty acids (PUFAs) depends, besides sufficient dietary intake, on efficiency of their endogenous biosynthesis by desaturation and elongation processes regulated by FA elongases and FA desaturases. Desaturases are encoded by PUFA desaturase genes (FADSs): FADS1 and FADS2. Alteration of FA desaturase activity and single nucleotide polymorphisms (SNPs) in the FADS1 and FADS2 gene cluster are associated with lipid metabolism dysfunction and may affect the pathogenesis of lipid-related diseases. People of different ages, from different ethnic backgrounds and countries may exhibit varying degrees of response to dietary supplements of ω3 and ω6 PUFAs. The study of the relationship between lipid metabolism disorders and genetic factors controlling FA metabolism is an important research area since the health effects of alimentary ω3 and ω6 PUFAs can depend on genetic variants of the FADS genes. This review summarizes the literature data on the association of FADS gene polymorphisms with lipid metabolism disorders and their role in the development of chronic non-communicable pathologies associated with changes in lipid metabolism.